Use of low dose irradiation as quarantine treatment for the oriental fruit fly (Bactrocera dorsalis Hendel) infested on the dragon fruit - Lam, Nguyen Duy; Diep, Tran Bang; Tu, Duong Minh (Academia Journal of Biology, 2015)
The potential of the gamma irradiation was investigated for the quarantine treatment of the oriental fruit fly (Bactrocera dorsalis Hendel) infested on the dragon fruit (Cereus undatus (Haw.)). For this purpose, we have studied the effects of the radiation treatment on the fly mortality and the fruit quality, and investigated technical parameters for the irradiation practice using the available irradiation facility of the Hanoi Irradiation Center. Results shown that 250 Gy is the minimal dose required for the quarantine treatment of the oriental fruit fly because it can be used to prevent the subsequent adult emergence and their reproduction from the third star larvae infesting the dragon fruit. The irradiation with 250 Gy and with higher doses (up to 600 Gy) did not affect the fruit appearance and the shelf-life. Several biochemical criteria such as vitamin C and reducing sugar were changed insignificantly. We reconfirmed that the irradiation with 250 Gy can be used as quarantine treatment for the dragon fruit infested by the oriental fruit fly.